Interactivity of iraqi daily newspapers sites an analytical study of the websites of al-mada,al-zaman.al-sabahand tareqal-shaab newspapers - Malah, Habeeb Khalaf (ALBAHITH ALALAMI, 2022)
A study of interactivity in the Iraqi newspaper sites_ An analytical study of the website of Al-Mada, Al-Zaman, Al-Sabah and Tariq Al-Shaab newspaper sought to determine the amount of interactivity in the sites of Iraqi newspapers that have been published since 2003, which consists of (15) newspapers according to the statistics of the Iraqi Books and Documents House.and the researcher conducted an analytical survey on these sites, and the percentage of interactivity in general was weak, not more than (47.1%), and this weakness in interactivity contributed greatly to the decline in surfers of the websites of those electronic newspapers.The highest aggregate rate of the research sample was in the simple interactive tools such as commenting, polls, benefit and subscription lists, and admiration, as it got a total of (75%), while the multiplicity of interactive options, which is one of the most interactive options and the most important in the international electronic newspaper sites, got a percentage (48.53%), which is very weak compared to its importance.The results of the research found that the monitoring system in the sites of the sample newspapers does not exceed (56.25%), which is a medium percentage indicating the weakness of the Iraqi electronic newspapers' websites in benefiting from these systems. The search results also showed that the websites of the Iraqi electronic newspapers are linked to the social networking site by (50%) in general, and the highest was the Facebook page by (100%), then Twitter, YouTube, Instagram after they were used by the sample newspapers by (75%), and Telegram , radio station, and Plus Google (25%).